Foliar application of IAA and GA3 on growth and yield attributes of mungbean (Vigna radiata L. R. Wilczek) - Nourin, Yeashina; Hoque, Md Ashabul; Islam, Mohammad Mahbub; Labib, Litun Ahmed; Dey, Swagata (Bangladesh Journal of Botany, 2024)
A field experiment was conducted to assess the effects of foliar application of Indole acetic acid (IAA) and Gibberellic acid (GA3) on the growth and yield of mungbean (BARI Mung-6) plants. Nine treatments were administered, including various concentrations of IAA and GA3, applied individually and in combination. The experiment followed a randomized complete block design (RCBD) with three replications, data were recorded on growth and yield parameters at 30 days after sowing (DAS) and at harvest. Results indicated that treatment T8 (IAA 50 mg/l + GA3 50 mg/l) significantly enhanced growth and yield attributes. Notably, T8 exhibited the highest values for plant height (57.50 cm), number of leaves per plant (47.33), number of branches per plant (7.67), chlorophyll content (55, SPAD value), shortest duration to 80% flowering (27.33) with 80% pod maturity (55.33), number of pods per plant (37.67), pod length (14.99 cm), number of seeds per pod (13.78), weight of 1000 seeds (54.95 g), seed yield (1.68 t/ha), biological yield (3.52 t/ha), and harvest index (47.73%). Conversely, the untreated control (T0) exhibited the lowest performance across all parameters. Therefore, foliar application of IAA and GA3, particularly at 50 mg/l concentration each, demonstrated significant improvements in growth, yield, and related attributes of mungbean. Bangladesh J. Bot. 53(3): 459-464, 2024 (September)